Optimization of Seed Bank Design with Window Placement Analysis in the Development Area of Forest and Germplasm Conservation in East Kalimantan - Arianti, Putri; Putra, Wahyu B.; Ferdiansyah, T. Fahmi; Harnomo, Fajar (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2025)
This study evaluates temperature conditions within the seed bank building at the National Forest and Germplasm Conservation Development (PKHPNN) in East Kalimantan, focusing on temperature control to ensure seed viability in a tropical environment. Thermal simulation results using Grasshopper Ladybug-Honeybee software indicate that the incubator and storage rooms meet the SNI standard, with temperatures ranging from 28.22°C to 28.71°C. However, the laboratory area has a maximum temperature of 28.62°C, exceeding the Ministry of Health’s standard of 26°C. A design modification addressed this issue by relocating the windows to the south side to reduce direct sunlight exposure. A re-simulation showed a temperature reduction to 26.43°C, though slightly above the maximum allowable limit. This study has several limitations, including excluding building material types, which can impact temperature stability. Additionally, humidity control factors were not analyzed, even though humidity plays a crucial role in seed storage. Therefore, further research should consider additional strategies such as selecting materials with better thermal insulation, implementing ventilation systems, and integrating passive cooling technologies to improve energy efficiency. With a more comprehensive approach, the seed bank building design can be optimized to maintain stable temperature and humidity while meeting established seed conservation standards.